2015
DOI: 10.1371/journal.pone.0123574
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 in Patients with Atrial Fibrillation Undergoing Radiofrequency Catheter Ablation

Abstract: BackgroundGalectin-3 (Gal-3) is an emerging biomarker in heart failure that is involved in fibrosis and inflammation. However, its potential value as a prognostic marker in atrial fibrillation (AF) is unknown. The aim of this study was to assess the impact of AF catheter ablation on Gal-3 and evaluate its prognostic impact for predicting rhythm outcome after catheter ablation.MethodsGal-3 was measured at baseline and after 6 months using specific ELISA. AF recurrences were defined as any atrial arrhythmia last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 23 publications
3
46
2
1
Order By: Relevance
“…Our data showed that PeAF patients had higher levels of circulating Gal-3 than SR control patients. This is in agreement with another study showing that persistent atrial fibrillation was an independent predictor of higher Gal-3 concentrations [11], and Gal-3 levels were found to be higher in patients with persistent atrial fibrillation and in those with cardiovascular risk factors [35]. With respect to sampling site differences, circulating Gal-3 in AF patients possibly originates not only from the heart but could also reflect systemic fibrosis and inflammation levels, and as reported previously, Gal-3 levels are higher peripherally than in intra-cardiac samples from patients undergoing catheter ablation for atrial fibrillation [30].…”
Section: Discussionsupporting
confidence: 93%
“…Our data showed that PeAF patients had higher levels of circulating Gal-3 than SR control patients. This is in agreement with another study showing that persistent atrial fibrillation was an independent predictor of higher Gal-3 concentrations [11], and Gal-3 levels were found to be higher in patients with persistent atrial fibrillation and in those with cardiovascular risk factors [35]. With respect to sampling site differences, circulating Gal-3 in AF patients possibly originates not only from the heart but could also reflect systemic fibrosis and inflammation levels, and as reported previously, Gal-3 levels are higher peripherally than in intra-cardiac samples from patients undergoing catheter ablation for atrial fibrillation [30].…”
Section: Discussionsupporting
confidence: 93%
“…Among the 38 full‐text articles assessed for eligibility, ten were excluded for the following reasons: One study lacked a control group; one study population was heart failure; four studies lacked available data for further analysis; and four reported duplicate data from studies that later published as full text . Finally, 28 studies involving 10 830 patients were included in our meta‐analysis, with their baseline characteristics shown in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…8 Galectin-3 has been associated with atrial remodeling in AF patients 9 and outcomes after catheter ablation of atrial AF. 10,11 Recent epidemiologic studies have shown that blood levels of galectin-3 are associated positively with incident heart failure (HF) and coronary heart disease (CHD), 6,1214 but to our knowledge, only 2 prospective studies of exclusively whites have tested whether galectin-3 concentrations are associated with incident AF. Both studies reported positive associations that were no longer significant after adjusting for traditional AF risk factors.…”
mentioning
confidence: 99%